1971
DOI: 10.1111/j.1532-5415.1971.tb05370.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination Medications in Psychiatric Treatment: Patterns in a Group of Elderly Hospital Patients*

Abstract: The patterns for treatment with combined medications were studied in a group of elderly male (N = 137) and female (N = 432) psychiatric patients housed in the continuedtreatment services of a state hospital. The combination most frequently used was that of an antidepressant agent with a tranquilizing drug (major or minor). Slightly more than half of all combinations of psychoactive agents prescribed for these patients were composed of a tranquilizer and an antidepressent agent.The combining of particular psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0
1

Year Published

1973
1973
1998
1998

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Despite temporal, geographic and institutional sample differences, the recent data generally are consistent with our earlier observations, i.e., the practice and patterns of combining two or more psychotropic drugs appears to be sex-related (2), age-related (1), and relatively independent of diagnosis or symptoms (5)(6)(7)(8)(9)(10). Additional data seem to support the conclusion that there is no sound theoretic or empiric rationale for the use of most psychotropic drug combinations (11).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Despite temporal, geographic and institutional sample differences, the recent data generally are consistent with our earlier observations, i.e., the practice and patterns of combining two or more psychotropic drugs appears to be sex-related (2), age-related (1), and relatively independent of diagnosis or symptoms (5)(6)(7)(8)(9)(10). Additional data seem to support the conclusion that there is no sound theoretic or empiric rationale for the use of most psychotropic drug combinations (11).…”
supporting
confidence: 81%
“…Since our initial surveys of pharmaceutical prescribing practices at a large state mental hospital (1,2), a number of reports describing patterns of psychoactive drug usage in psychiatric hospitals have appeared in the literature (3,4). In view of the previous paucity of data on this subject, this increment almost qualifies as an "information explosion."…”
mentioning
confidence: 95%
“…The use of psychoactive medications in nursing homes has been reported for more than 4 decades 1–4 . With the growing number of pharmacologic agents, expansion into clinical geriatric practice followed, 5 particularly in nursing homes where a majority of residents have psychiatric illnesses 6–9 . Reported rates of psychoactive drug use in US nursing homes ranges from 11% 10 to 35% 11,12 to nearly 90%, 13 with the majority of studies reporting rates of greater than 50% 14–25 .…”
mentioning
confidence: 99%
“…A study of 539 older male and female psychiatric patients treated with drug combinations (polypharmacy) at Central Islip State Hospital has indicated that the pattern of polypharmacy appears to be an age-related phenomenon (1). The use of major tranquilizers as part of a drug combination decreased with increasing age of the patients, while the use of minor tranquilizing agents increased.…”
mentioning
confidence: 99%